ANALISIS CUSTOMER VALUE PADA MY SALON INTERNATIONAL DI MALL CIPUTRA SERAYA PEKANBARU - Musfar, Tengku Firli; Parlina, Rani (Jurnal Ekonomi, 2014)
Customer- oriented is a marketing strategy that applies in many company recentlybecause it is important to know the value of the delivered product/service from thecustomer perspective. That’s why, writer interested to know how is the customervalue at My Salon International on Ciputra Seraya Mall Pekanbaru. This studybased on the definition of customer value that declared by Philip Kotler which is,Customer Value is the different between Perceived Benefit toward Perceived Costof Purchase. Perceived benefit variable consist of 4 dimensions; product value,service value, personal value, and image value. On the other side, perceived costof purchase variables consist of cost, time, and energy. The highest benefit thatdelivered to the customer with the lowest sacrifice that that given by the customer,will gives the positive customer value company in the customer perspective. Toreach the competitive best value, company has to provide the superior value bygiving the best benefit with the lowest sacrifice.Collecting data technique by spread the questioner to the respondent, total sampleis 100 respondents and the respondents chosen by quota accidental samplingtechnique. Analysis method that used in this study is qualitative and quantitativeanalysis method. By describes the scoring result on each attribute of perceivedbenefit and perceived cost of purchase variable.The result on each attributes score from both variable of customer value,concluded that customer value at My Salon International on Ciputra Seraya MallPekanbaru is positive because the delivered benefit is higher than the customersacrifice, that is 3,59 > 2,48. On the perceived benefit variable known that therespondents agree to the average range scale. Company delivered benefit thatgiving the highest contribution toward positive customer value with averagerange scale 4.05 according to the respondents is personal value. It means thatrespondent agree to all of the attributes of the personal value in the questioner.But, the dimension image value the customer responses on average range quiteagree. That happens because the weak of the image that company performs. Andto the perceived cost of purchase variable, customer give a good response toevery attributes of the dimensions, such as cost, time and energy because theaverage range scale from all dimensions stand on agree level.It proven that My Salon International on Ciputra Seraya Mall Pekanbarufacilitated the customer with the supports facility system that makes customerearn the benefit of the product/service with fast and accurate time and energy.Besides, My Salon International Ciputra Seraya Mall of Pekanbaru offeringaffordable price.Keywords : Customer value, perceived benefit and perceived cost of purchase